2016
DOI: 10.1007/s40266-016-0390-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Sunitinib in Elderly Patients with Metastatic Renal Cell Carcinoma: Data from Real-World Clinical Practice

Abstract: The differences in patient profile and dose-reduction rates point to a different approach in the management of older and younger patients in daily clinical practice. The lower dose intensity of sunitinib in the elderly population may have translated into inferior survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 13 publications
1
18
0
1
Order By: Relevance
“…The other possible explanation for the improved prognosis for older patients is optimal management of a therapeutic schedule personalized for each patient. Several previous studies have demonstrated the efficacy and safety of various agents [e.g., sunitinib (6,(15)(16)(17)(18) and sorafenib (19)] for older patients, and another study reported that an alternative schedule of sunitinib treatment provided a greater improvement in the OS rate compared with the standard schedule (20). Since sunitinib was prescribed on the basis of a personalized schedule in the later period, the data from our present study for patients treated with sunitinib is consistent with those reports (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The other possible explanation for the improved prognosis for older patients is optimal management of a therapeutic schedule personalized for each patient. Several previous studies have demonstrated the efficacy and safety of various agents [e.g., sunitinib (6,(15)(16)(17)(18) and sorafenib (19)] for older patients, and another study reported that an alternative schedule of sunitinib treatment provided a greater improvement in the OS rate compared with the standard schedule (20). Since sunitinib was prescribed on the basis of a personalized schedule in the later period, the data from our present study for patients treated with sunitinib is consistent with those reports (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…It would be reasonable to therefore question if the reported efficacy and safety of sunitinib was applicable to the elderly population. Our analysis included two RWD studies in elderly patients; each study population had a median age of 74 years and mPFS and mOS were consistent with the combined confidence estimate and phase III RCT [11,38,46]. Furthermore, several RWD studies have found no significant difference in PFS or OS between patients aged ≥ 70 years and those aged < 70 years [46,[59][60][61].…”
Section: Discussionmentioning
confidence: 85%
“…RWD studies used a variety of sources to extract data, including national and local cancer registries, insurance databases, pharmacy databases, and patient medical records [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Studies were from a wide range of countries, including USA, Canada, Australia, Spain, France, Greece, Italy, Netherlands, Czech Republic, China, Japan, Korea, and India.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…The efficacy and safety of sunitinib in treatment‐naive patients with advanced clear cell RCC was demonstrated in the pivotal phase III trial, in which sunitinib significantly prolonged median progression‐free survival (mPFS) but not overall survival (OS) versus IFN‐α (Table ). Several real‐world studies confirm the effectiveness of first‐line sunitinib in patients with aRCC . Most large ( n > 150) real‐world studies are retrospective, multicenter analyses with a wide range in mPFS (7.0–20.0 months) and median OS (mOS; 18.7–45.1 months) reported across studies .…”
Section: Introductionmentioning
confidence: 94%
“…Several real‐world studies confirm the effectiveness of first‐line sunitinib in patients with aRCC . Most large ( n > 150) real‐world studies are retrospective, multicenter analyses with a wide range in mPFS (7.0–20.0 months) and median OS (mOS; 18.7–45.1 months) reported across studies . In one of the larger real‐world sunitinib studies that provided information about the effectiveness in patient subgroups often excluded from clinical trials, an expanded‐access trial in 4,543 patients with metastatic RCC demonstrated that the objective response rate (ORR) was 16% and mPFS and mOS were 9.4 and 18.7 months, respectively .…”
Section: Introductionmentioning
confidence: 99%